2008
DOI: 10.1097/bot.0b013e31815b35aa
|View full text |Cite
|
Sign up to set email alerts
|

Amputations in U.S. Military Personnel in the Current Conflicts in Afghanistan and Iraq

Abstract: Overall, major limb amputation rates for the current U.S. engagement in Afghanistan and Iraq are similar to those of previous conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 8 publications
4
65
1
2
Order By: Relevance
“…In total, only 103 (11%) servicemembers with amputation had a final rating of COAD, and 16 (2%) servicemembers with amputation had a final duty status of Fit ( Table 1). The mean age (24.0 yr), median rank (Enlisted 4) and percentage male (98.4%) demonstrated that this cohort was demographically consistent with previous studies of wounded servicemembers [3][4][10][11]. There were significantly more Air Force servicemembers with amputation found Fit than in other branches of service (p < 0.001), and no Marine or Navy servicemembers with amputation were found Fit.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In total, only 103 (11%) servicemembers with amputation had a final rating of COAD, and 16 (2%) servicemembers with amputation had a final duty status of Fit ( Table 1). The mean age (24.0 yr), median rank (Enlisted 4) and percentage male (98.4%) demonstrated that this cohort was demographically consistent with previous studies of wounded servicemembers [3][4][10][11]. There were significantly more Air Force servicemembers with amputation found Fit than in other branches of service (p < 0.001), and no Marine or Navy servicemembers with amputation were found Fit.…”
Section: Resultssupporting
confidence: 70%
“…There has been a substantial number of amputations among U.S. servicemembers involved in OIF, OEF, and OND [3][4]10,[12][13]. Depending on severity, treatments rendered, and rehabilitation, many servicemembers are unable to return to Active Duty status following amputation [3][4]9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extremity trauma accounts for over 70% of battlefield injuries [36] and is also the most common injury seen in civilian trauma centers. Morbidity is high when limb injury is complicated by ischemia, often resulting in residual disability or even amputation [26,32].…”
Section: Introductionmentioning
confidence: 99%